The Role of Ahadhiyah Schools in Fostering Student Moral Values: An Empirical Study based on Kegalle District, Sri Lanka - Mohamed Nisardeen Fathima Nishada; Iqbal, Saujan; Ahmed Sarjoon Razick (LECTURES: Journal of Islamic and Education Studies, 2025)
Educational institutions contribute to both religious and secular education by helping students grow in their morals and ethical values to turn them into responsible persons in society. During the colonial period in Sri Lanka, various religious schools were established to achieve this goal. Within the institution, Ahadhiyah schools were formed in 1951 to improve Muslim students’ ethical and moral standards by providing Islamic education. These days, Ahadhiyah schools are having difficulty promoting moral values, and this has led to more problems with student behaviour. In this background, the present study aims to identify Ahadhiyah schools’ role in developing students’ moral and ethical values. 285 students currently attending Ahadhiyah schools in Kegalle district of Sri Lanka, took part in a questionnaire survey conducted by researchers. The convenience sampling method was used to choose the sample. Besides, parents, principals, and educated individuals were interviewed in an unstructured manner, and the analysis was done using the coding method. The findings of the study indicate that the Ahadhiyah schools within the designated area have been ineffective in fostering the moral development of students, resulting in various manifestations of selfishness, rivalry, jealousy, disrespect towards elders, and discrimination. Furthermore, the number of truant students has been increasing due to traditional teaching methods, and parents are not adequately fulfilling their responsibility of ensuring their children's proper attendance at schools, further impeding the development of moral values. This study provides valuable insights aimed at enhancing the effectiveness and raising awareness of Ahadhiyah schools for positive change. The Kegalle District Ahadhiya School's and Central Ahadhiyah Federation will use the findings to guide future decision-making.